HEGEMONI EPISTEMOLOGI RASIONAL BARAT DALAM KONSTRUKSI KURIKULUM PAI DI INDONESIA - Rustan Efendy (IAIN PAREPARE, 2015)
Construction of Curriculum 2013 islamic religious education subjects can not be separated from the influence of the world in terms of epistemology is the epistemology of the West, the indicator is the ratio of the dominant use in the learning process, where the ratio is a key tool in the philosophy of rational epistemology West. This paper discusses the West's hegemony rationalism construction PAI Curriculum 2013 subjects who dissect the influence of Western rationalism epistemology in Curriculum 2013 subjects PAI. Analysis of the data used in this paper is the analysis of documents that a thorough analysis of curriculum documents in 2013 subjects PAI. Findings is that the curriculum in 2013 on the subjects of PAI greatly affected even hegemony by Western rationalism.